Опыт работы пренатального консилиума в Запорожской области за период 2011-2015 гг. - Авраменко, Н. В.; Ломейко, Е. А.; Никифоров, О. А.; Сухонос, О. С.; Авраменко, Наталія Вікторівна; Ломейко, Олена Олександрівна; Нікіфоров, Олег Анатолійович; Сухонос, Оксана Сергіївна; Avramenko, N. V.; Lomeyko, H. A.; Nikiforov, O. A.; Sukhonos, O. S. (My University, 2017)
У статті представлені основні напрямки роботи медико-генетичної служби Запорізької області з діагностики та попередження народження дітей зі спадковими і вродженими захворюваннями. Проаналізовано досвід роботи пренатального консиліуму на базі клініки Запорізького обласного центру репродукції людини за період 2011–2015 рр. Aim. In the article the basic directions of work of medical genetic services Zaporizhzhia region on the diagnosis and prevention of birth of children with hereditary and congenital diseases. The experience of the work of prenatal consultation at the clinic of Zaporizhzhia Regional Center of Human Reproduction for the period 2011–2015. Congenital malformations is one of the main causes of high infant mortality and disability from childhood. Medical and genetic counseling is an important integral part of prenatal diagnosis. The main document regulating prenatal diagnosis is the order of the Ministry of Health of Ukraine number 641/84 dated 31.12.2003 «On the improvement of medical and genetic services in Ukraine.» According to the order of early diagnosis, prevention of congenital and hereditary diseases is one of the main objectives of the regional medical genetic counseling. To this end, for the early detection and prevention of birth of children with hereditary diseases in the Zaporizhzhia region using modern methods of prenatal diagnosis, including mass and selective testing of pregnant women on birth defects and chromosomal abnormalities by ultrasound examination and evaluation of maternal serum markers, as well as prenatal, cytogenetic diagnosis of chromosomal diseases in high-risk groups. Methods and results. The clinic Zaporizhzhia Regional Center for Human Reproduction in the prenatal consultation for the period 2011–2015 examined 2528 pregnant women with suspected congenital malformations of the fetus. Once the diagnosis of pregnant women consulted a geneticist, obstetrician – gynecologist, others specialists to adequately assess the perinatal prognosis and develop tactics of pregnancy and the patient in the early neonatal period. In a study on prenatal consultation for the period of 2011–2015 years from 1435 pregnant women were identified congenital malformations of the fetus. Recommendations for the management of pregnant women in the presence of disorders of fetal development were given prenatal consultation, including doctors of several specialties: genetics, ultrasound doctor, obstetrician pediatric surgeon, heart surgeon, urologist, specialists in the profile. Conclusion. In identifying chromosomal aberrations and congenital malformations in the fetus prenatal consultation defines: the forecast for the life and health of the child, the tactics of pregnancy and delivery, postnatal correction.
Досвід роботи пренатального консиліуму в Запорізькій області за період 2011–2015 рр.
Experience of prenatal consultation in the Zaporozhye region over the period 2011-2015
Keywords: вроджені вади розвитку; пренатальна діагностика; медико-генетична служба; пренатальний консиліум; congenital malformations; prenatal diagnosis; medical genetic services; prenatal consultation